Implications of labour migration for rice production and household economy: Evidences from eastern India - SINGH, K M; SINGH, R K P; KUMAR, ANJANI; KUMAR, ABHAY; MEENA, M S; CHAHAL, V P (The Indian Journal of Agricultural Sciences, 2015)
The study evaluates the extent, impact and determinants of labour migration in Bihar. Data were collected in 2011 from four hundred households (200 migrants and 200 non-migrants) four villages, each of rainfed ecosystem (Madhubani district) and partially irrigated ecosystem (East Champaran district). Non-linear model (Cobb-Douglas) was used to find out impact of migration on input efficiencies in rice production. Regression coefficients (Î²) were computed for major factors of production. Probit model employed to measure the determinants of migration. Study reveals that youngsters are more prone to migration to urban centers for non-farm activities. Migration helped in rational use of two critical inputs, i.e. labour and irrigation in rice production. Judicious use of human labour wasalso observed at native place due to migration of surplus labour. However, potential of land and capital (seeds, fertilizers and agricultural chemicals) are still to be exploited on both categories of households. Migrants remittance utilized for meeting consumption need, better education to children, improved housing and better health care facilities. Remittances helped in improving livelihoods of migrant households. Migration also inculcated saving habits amongst migrants. It emerged as risk-coping strategy for weaker sections of society. Allocation of remittances on agricultural inputs could have increased if proper infrastructure facilities were made available in rural areas for faster dissemination of modern agricultural technologies. Male member of lower caste having large land size and dependents is more prone to migration. Caste barrier in migration has weakened in Bihar but still persist, however, size of farm is no more taboo.